Perencanaan Sistem Akuntansi Penerimaan Kas pada Perusahaan Jasa AC “Maulana Tehnik” - Hartanto, Boby; Pratiwi, Yanna Eka; Lastiani, Siwidyah Desi (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
This study aims to examine the existing cash accounting information system at Maulana Teknik, and then design an appropriate cash accounting information system for its application. This study used observation, interviews, and analysis of records as information gathering techniques. The information gathered is then juxtaposed with theoretical concepts to identify gaps between theory and real-world practice. Research tools include questionnaires and documentation of cash receipts. The development process includes analysis, planning, and implementation phases. The investigation yielded the following insights: First, Maulana Teknik's current accounting system consists of several functions related to cash receipts, including order placement, service provision, cash handling, and savings tracking. Records are maintained through daily AC service reports, supported by invoices. Procedures include placing orders, delivering services, handling cash, recording sales, and plotting cash receipts flow charts. However, the available internal control systems were limited and deviated from theoretical norms. Second, the accounting system designed for Maulana Teknik includes an analysis phase, uncovering the deficiencies of the old system and the potential of the new system. The design phase includes procedures, accounting records, documents, flow charts, and internal control systems. Finally, the implementation phase involves employee training, testing of the new system, analysis of test results and finally system conversion.